1988
DOI: 10.1172/jci113606
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of contractile dysfunction with oxidative energy production and tissue high energy phosphate stores during partial coronary flow disruption in rabbit heart.

Abstract: The relationships between contractile function, myocardial oxygen consumption, and tissue high energy phosphate and lactate content were investigated during partial coronary flow disruption. The experimental preparation was an isolated, isovolumic retrograde blood-perfused rabbit heart. Both developed pressure (r = 0.94) and dp/dt (r = 0.95) exhibited strong linear correlations with myocardial oxygen consumption that were stable for up to 45 min after blood flow reduction. In contrast, tissue high energy phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2
1

Year Published

1991
1991
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 24 publications
0
12
2
1
Order By: Relevance
“…4 a) (8) showed a relationship between decreases in coronary perfusion pressure and a fall of PCr/Pi in the perfused rat heart. However, several perfused heart studies have suggested that the fall in contractility associated with mild coronary flow reductions occurs without changes in cardiac energy phosphates (6,7,14,15 The present study, which demonstrates a significant increase of Pi at a coronary flow to 75% of control, differs in several ways from the aforementioned reports. The signal/ noise ratio of the 3"P-MRS spectra was substantially improved by acquiring data over 10-min steady state periods of mild coronary flow reductions.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…4 a) (8) showed a relationship between decreases in coronary perfusion pressure and a fall of PCr/Pi in the perfused rat heart. However, several perfused heart studies have suggested that the fall in contractility associated with mild coronary flow reductions occurs without changes in cardiac energy phosphates (6,7,14,15 The present study, which demonstrates a significant increase of Pi at a coronary flow to 75% of control, differs in several ways from the aforementioned reports. The signal/ noise ratio of the 3"P-MRS spectra was substantially improved by acquiring data over 10-min steady state periods of mild coronary flow reductions.…”
Section: Discussioncontrasting
confidence: 95%
“…Although the increase of Pi was relatively small at this level ofcoronary flow reduction, it was ofa magnitude that has been associated with marked reductions of force and an alteration of the calcium-force relationship in skinned myofiber studies ( 12,13). In contrast, previous perfused heart studies (6,7,14,15) reported no change in energy phosphates as measured by 31P magnetic resonance spectroscopy (31P-MRS) during mild coronary flow reductions (i.e., 50-99% of 1. Abbreviations used in this paper: ACa., cytosolic free calcium transient amplitude; dCah, diastolic calcium; F385/F454, ration of Indo-l fluorescence intensities at emission wavelengths of 385 and 454 nm; 5F-BAPTA, 5,5'-difluoro derivative of l,2-bis-(o-aminophenoxy)ethane-N,N,N',N'-tetraacetic acid; MPA, methylphosphonic acid; Pi, inorganic phosphate; 3'P-MRS, 3'P magnetic resonance spectroscopy.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…We used an isolated, isovolumic, working red cell-perfused heart preparation that was developed in our laboratory based on the work of Marshall (8) and has been described previously in detail (6,7,9 (10) and has been previously reported (1 1). The heart was then placed in a water-jacketed constant temperature chamber and submerged in saline.…”
Section: Experimental Preparationmentioning
confidence: 99%
“…A red cell perfusate as previously described (7,8) RNA isolation and Northern blot analysis. At the completion of nonischemic perfusion protocols the left ventricle was flushed with saline to remove the blood, dissected from the right ventricle, and then frozen in liquid nitrogen.…”
Section: Experimental Preparationmentioning
confidence: 99%